The Twilight Zone - Season One Episode 1-36 - Stevens, Robert; Parrish, Robert; Reisner, Allen; Leisen, Mitchell; Smight, Jack; LaShelle, Joseph; Clemens, George T.; Landau, Martin; Warden, Jack; Meredith, Burgess (2 entertain Video, 2005)
The Twilight Zone is generally considered to be the first real "adult" science-fantasy anthology series to appear on American television, introducing the late 1950s TV audience to an entertaining and at the same time thought-provoking collection of human condition stories wrapped within fantastic themes. Although the series is usually labeled a science fiction program its true sphere was fantasy, embracing elements of the supernatural, the psychological, and "the almost-but-not-quite; the unbelievable told in terms that can be believed" (Rod Serling). [www.museum.tv]
Keywords: DVD-Video